Research Progress of Shape Memory Polymers in Biomedical Fields - Lin, Xinwang (Transactions on Environment, Energy and Earth Sciences, 2026)
When external stimulation is applied, Shape Memory Polymer (SMP) can maintain its shape and spontaneously revert to its initial form when the stimulation is removed. With the increasing demand for smart materials in biomedical engineering, shape memory polymers have attracted extensive attention due to their unique stimulus-responsive properties. Because of their superior qualities, SMPs are progressively being utilized in the biomedical industry. SMPs are currently employed in biological domains, including tissue repair, drug delivery, and surgery. This thesis summarizes the high stretchability, biodegradability, and biocompatibility of SMPs. It also details their fundamental operating mechanisms and four common actuation types (thermal-responsive, light-responsive, electric-responsive and chemical-responsive). The thesis also highlights the current clinical applications of SMPs in drug delivery, dentistry, and tissue regeneration. Systematic research on the multi-response mechanism of SMP and its applications in biomedicine is conducive to promoting the innovative development of intelligent medical devices in the field of precision medicine.